Combined headspace single-drop microextraction and solid-phase microextraction for the determination of phenols as their methyl ethers by gas chromatography-mass spectrometry. Issue 46 (17th November 2017) - Jain, Archana; Soni, Soumitra; Reddy-Noone, Kishan; Pillai, Aradhana K. K. V.; Verma, Krishna K.
Abstract : A combination of headspace large volume single drop extraction and solid phase microextraction permitted attainment of high sensitivity by transferring an overall large mass of analytes into a gas chromatograph. Abstract : Combined SDME and SPME worked as an elegant strategy to inject a large sampled mass of analytes into a GC. After headspace SDME of methyl derivatives of phenol, chlorophenols, methylphenols and other substituted phenols into 10 μL of solvent drop (1-butanol), the extract was subjected to headspace SPME (DVB/CAR/PDMS, 30/50 μm, fiber) for convenient transfer of analytes to the fiber and then into the GC. This combination resulted in achieving a high sensitivity of detection for a small volume (0.5–2 mL) of sample. The chromatographic separation of thirteen model phenols (as their methyl ethers) was complete within 10 min. A rectilinear calibration graph was obtained using combined headspace SDME/SPME and GC-MS in the range of 0.001–5 mg L −1, with a correlation coefficient of 0.990–0.999 and an average limit of detection of 20 ng L −1 (range 8–45 ng L −1 ), which was far better than that obtained by headspace SDME, 90 ng L −1 (range 50–138 ng L −1 ), or headspace SPME, 55 ng L −1 (range 36–70 ng L −1 ), when used alone. In spiking experiments on environmental water samples, the RSD of the results was in the range of 4.6–9.4%.